Multicenter analysis of stereotactic radiotherapy of the resection cavity in patients with brain metastases - Stephanie E. Combs; Angelika Bilger; Christian Diehl; Eva Bretzinger; Hannah Lorenz; Oliver Oehlke; Hanno M. Specht; Anna Kirstein; Anca‐Ligia Grosu (Cancer Medicine)
Abstract Brain metastases show a recurrence rate of about 50% after surgical resection. Adjuvant radiotherapy can prevent progression; however, whole‐brain radiotherapy (WBRT) can be associated with significant side effects. Local hypofractionated stereotactic radiotherapy (HFSRT) is a good alternative to provide local control with minimal toxicity. In this multicenter analysis, we evaluated the treatment outcome of local HFSRT after resection brain metastases in 181 patients. Patient's characteristics, treatment data as well as follow‐up data were collected and analyzed with special focus on local control, locoregional control and survival. After a median follow‐up of 12.6 months (range 0.3–80.2 months), the crude rate for local control was 80.5%; 1‐ and 2‐year local recurrence‐free survival rates were 75% and 70% (median not reached). Resection cavity size was a significant predictor for local recurrence (P = 0.033). The median overall survival was 16.0 months. Both graded prognostic assessment score and recursive partitioning analysis were accurate predictors of survival. HFSRT leads to excellent local control and has a high potential to consolidate results after surgery; acute and late toxicity is low. Distant intracerebral metastases occur frequently during follow‐up, and therefore, a close patient monitoring needs to be warranted if whole‐brain radiotherapy is omitted.